Revisiting the Immunological Aspects of Temozolomide Considering the Genetic Landscape and the Immune Microenvironment Composition of Glioblastoma - Di Ianni, Natalia; Maffezzini, Martina; Eoli, Marica; Pellegatta, Serena (Frontiers in Oncology, 2021)
The microenvironment (ME) plays a critical role in causing glioblastoma (GBM) to be a moving and incurable target. The main features governing the interaction between cancer cells and the ME include dependency, promotion, and in rare cases, even competition. In the original Stupp protocol, the alkylating agent temozolomide (TMZ) is the first-line chemotherapy drug to treat GBM, and it is broadly used together or after radiotherapy. Some studies have described TMZ as an adjuvant to other therapeutic approaches including immunotherapy because of its ability to induce an immunogenic death of cancer cells. TMZ also exerts immunomodulatory effects on the tumor and immune ME. These findings support the coexistence of two circuits, i.e., one that subverts local immunosuppressive mechanisms and another that exerts a harmful influence on the peripheral immune response. A bias toward the latter can drive the failure of treatments based on the combination of chemotherapy and immunotherapy approaches. In this review, we will reanalyze how intrinsic and acquired resistance to TMZ impacts the immunomodulatory effects previously described by way of inducing a functional alteration of local immune cells and promoting immunosuppression and how different components of the immune ME, with particular attention to tumor-associated macrophages and microglia, can cause TMZ resistance to circumvent potential local immunogenic mechanisms.